Evolving Landscape of New Drug Approval in Japan and Lags from International Birth Dates: Retrospective Regulatory Analysis. Issue 5 (15th November 2020) - Tanaka, Mototsugu; Idei, Mayumi; Sakaguchi, Hiroshi; Kato, Ryosuke; Sato, Daisuke; Sawanobori, Kenji; Kawarasaki, Shuichi; Hata, Toshiyuki; Yoshizaki, Asako; Nakamura, Miki; Ikuma, Mutsuhiro
Abstract : The Pharmaceuticals and Medical Devices Agency (PMDA) has approved hundreds of new drugs in recent years. We retrospectively analyzed the new drugs approved in Japan from 2008 to 2019, and identify the first‐in‐world approvals and clarify the current drug lag. The new drug and the drug lag were defined as a drug with a new active substance and a difference between the approval date in Japan and the international birth date, respectively. Among 400 new drugs approved in Japan during the last 12 years, 80 (20.0%) were first approved in Japan, and 320 were outside Japan (the United States: 202, 50.5%; Europe: 82, 20.5%; other regions: 36, 9.0%). Of these, 45 new drugs have not yet been approved outside Japan, and the remaining 355 have been globally approved in Japan and overseas. The number of new drug approvals were the largest in oncology followed by metabolic/endocrine and infectious diseases. The median drug lags (year) among all 400 new drugs and 355 new drugs with global approvals were 4.3 and 4.7 in the first tertile (2008–2011), 1.5 and 2.6 in the second tertile (2012–2015), and reduced to 1.3 and 2.2 in the third tertile (2016–2019), respectively. Substantial drug lag remains in neurology, psychiatry, and therapeutic areas where the number of new drug approvals was relatively small. Collectively, one‐fifth of the new drugs approved in Japan are first‐in‐world approvals. Drug lag has been greatly decreased, although it still exists.